2018
DOI: 10.1063/1.5002132
|View full text |Cite
|
Sign up to set email alerts
|

Covalent nitrogen doping in molecular beam epitaxy-grown and bulk WSe2

Abstract: Covalent p-type doping of WSe2 thin films grown by molecular beam epitaxy and WSe2 exfoliated from bulk crystals is achieved via remote nitrogen plasma exposure. X-ray photoelectron and Raman spectroscopies indicate covalently bonded nitrogen in the WSe2 lattice as well as tunable nitrogen concentration with N2 plasma exposure time. Furthermore, nitrogen incorporation induces compressive strain on the WSe2 lattice after N2 plasma exposure. Finally, atomic force microscopy and scanning tunneling microscopy reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…A clear blue shift of E 1 2g/A1g and 2LA(M) was observed after the 250 °C treatment. According to previous studies 37,39 , the blue shift (~ 1.3 cm -1 ) in the E 1 2g/A1g peak is correlated to p-type doping effect in WSe2 flakes, which is consistent with our XPS analysis and electrical characterizations discussed in the later paragraph. Therefore, we have confirmed that both atomically precise layer control and doping level modulation can be achieved through different treatment temperatures.…”
Section: Materials Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…A clear blue shift of E 1 2g/A1g and 2LA(M) was observed after the 250 °C treatment. According to previous studies 37,39 , the blue shift (~ 1.3 cm -1 ) in the E 1 2g/A1g peak is correlated to p-type doping effect in WSe2 flakes, which is consistent with our XPS analysis and electrical characterizations discussed in the later paragraph. Therefore, we have confirmed that both atomically precise layer control and doping level modulation can be achieved through different treatment temperatures.…”
Section: Materials Analysessupporting
confidence: 91%
“…Lower binding energy suggests that more prominent doping effect can be achieved at higher temperature treatment. 37,38 The doping effect in WSe2 was also examined by Raman spectroscopy. Figure 2g compares the Raman spectra of WSe2 flakes before and after the O2 plasma treatment at 250 °C.…”
Section: Materials Analysesmentioning
confidence: 99%
“…Two prominent Raman peaks at 150.2 cm −1 and 211.0 cm −1 are assigned to E g -like and A g -like vibrational modes, respectively [51]. In TMDs, Raman active modes have been reported to shift with changes in strain [52], temperature [53], and doping [54]. Figure 2d confirms that ReS 2 remains unaffected following the annealing and the ALD process.…”
Section: Resultsmentioning
confidence: 81%
“…[39] Notably, Raman peak shift is usually inevitable for TMD materials when carrier doping or strain is introduced, so the unchanged eigen-peak positions revealed that the possibility of carrier concentration variation or lattice strain induced by air-exposure can be ruled out. [19,[40][41][42] The wavenumber difference between the two eigen-peaks is ~ 8 cm -1 for both F-WSe2 and O-WSe2, suggesting BL configuration for F-WSe2. [33] The wavenumber difference of WSe2 shows evident dependence on thickness and no peak of tungsten oxide (or seledium oxides) was observed (see the magenta…”
Section: Resultsmentioning
confidence: 94%